Hydroquinone Increases 5-Hydroxymethylcytosine Formation through Ten Eleven Translocation 1 (TET1) 5-Methylcytosine Dioxygenase - Coulter, Jonathan B. (American Society for Biochemistry and Molecular Biology, 2013)
DNA methylation regulates gene expression throughout development and in a wide range of pathologies such as cancer and neurological disorders. Pathways controlling the dynamic levels and targets of methylation are known to be disrupted by chemicals and are therefore of great interest in both prevention and clinical contexts. Benzene and its metabolite hydroquinone have been shown to lead to decreased levels of DNA methylation, although the mechanism is not known. This study employs a cell culture model to investigate the mechanism of hydroquinone-mediated changes in DNA methylation. Exposures that do not affect HEK293 cell viability led to genomic and methylated reporter DNA demethylation. Hydroquinone caused reactivation of a methylated reporter plasmid that was prevented by the addition of N-acetylcysteine. Hydroquinone also caused an increase in Ten Eleven Translocation 1 activity and global levels of 5-hydroxymethylcytosine. 5-Hydroxymethylcytosine was found enriched at LINE-1 prior to a decrease in both 5-hydroxymethylcytosine and 5-methylcytosine. Ten Eleven Translocation-1 knockdown decreased 5-hydroxymethylcytosine formation following hydroquinone exposure as well as the induction of glutamate-cysteine ligase catalytic subunit and 14-3-3σ. Finally, Ten Eleven Translocation 1 knockdown decreased the percentage of cells accumulating in G(2)+M following hydroquinone exposure, indicating that it may have a role in cell cycle changes in response to toxicants. This work demonstrates that hydroquinone exposure leads to active and functional DNA demethylation in HEK293 cells in a mechanism involving reactive oxygen species and Ten Eleven Translocation 1 5-methylcytosine dioxygenase.